Higher dietary butyrate intake is associated with better cognitive function in older adults: evidence from a cross-sectional study - Tu, Jiayu; Zhang, Jun; Chen, Gang (Frontiers in Aging Neuroscience, 2025)
BackgroundStudies indicate that butyrate can enhance memory and cognitive functions in mice by inhibiting neuroinflammation and neuronal apoptosis. Elevated fecal butyrate levels in older individuals with mild cognitive impairment correlate with reduced levels of Aβ-42, an Alzheimer’s disease biomarker. This study investigated the relationship between butyrate consumption and cognitive performance in older adults, which remains to be elucidated.MethodsThis study employed a cross-sectional, observational design to analyze data gathered from 2,078 participants enrolled in the 2011–2014 US National Health and Nutrition Examination Survey (NHANES). Butyrate intake was determined based on two 24-h dietary assessments. To evaluate cognitive function, three tests were administered: the Animal Fluency Test (AFT) to assess executive function, the Digit Symbol Substitution Test (DSST) for measuring processing speed, and the Consortium to Establish a Registry for Alzheimer’s disease (CERAD) subtest for assessing memory. Z scores were computed for each test and overall cognitive performance. Multivariate linear regression models and a generalized additive model (GAM) were used to examine the correlation between butyrate consumption and mental functions. Finally, subgroup analyses and interaction tests were used to verify the robustness of the associations.ResultsThe NHANES study encompasses two surveys conducted between 2011 and 2014 that involved 2,078 participants aged 60 years or older. Higher dietary butyrate consumption had a positive correlation between superior performance on DSST, AFT, CERAD-Immediate Recall Test, and Z scores. The participants in the upper quartile of butyrate intake had significantly higher DSST (β = 1.60, 95% CI: 0.04–3.17), AFT scores (β = 0.99, 95% CI: 0.37–1.60), and Z scores (β = 0.09, 95% CI: 0.01–0.17) than individuals in the lowest quartile even after adjusting for potential confounders. Finally, no notable interactions were observed within the groupings. Finally, in subgroup analyses, BMI was found to influence the positive association between butyrate and DSST with Z score, and hypertension also influenced the association between butyrate and DSST.ConclusionHigher butyrate intake in individuals aged ≥60 years was linked to better cognitive functioning. This could potentially contribute to maintaining brain function during aging.